Maximizing Local Potential in Family and Community-Based Village Enterprise Management in Dooro Village, Gresik - Akbar, Rasyidi Faiz; Andjarwati, Anik Lestari; Putra, Syaifurrizal Wijaya; Ramadhan, Dyandra Armyta (LPPM Universitas Muhammadiyah Tasikmalaya, 2025)
This community service program aims to empower the BUMDes and Sekoper groups in Dooro Village, Gresik, addressing challenges in entrepreneurship, financial literacy, and digitalisation. The method for this community service is by giving a short training. The program integrates tailored workshops on business management, marketing, financial planning, and e-commerce. Participants engaged in hands-on practices, such as financial record-keeping and digital marketing, to apply acquired skills effectively. Key outcomes include enhanced entrepreneurial knowledge, improved financial management practices, and increased adoption of digital tools. The results can be shown in post-training evaluations, which showed a significant improvement in participants' financial literacy, with 92% achieving high assessment scores. The program also fostered collaboration with local stakeholders, promoting sustainable development. Plans include advanced training, mentoring, and partnerships to enhance market access and strengthen business operations. The conclusion of this initiative demonstrates is this community service can be a replicable model for community empowerment, combining tailored training with strategic collaboration to address local economic challenges and unlock community potential.